Response of old and new cowpea varieties to insecticide spray regimes in the Sudan savanna of Nigeria - Kamara, A.; Ewansiha, S.U.; Ajeigbe, Hakeem A.; Omoigui, L.O. (Informa UK Limited, 2013)
Insect pests are major constraint to cowpea production in northern Nigeria causing yield losses up to 70%. Several cowpea varieties have been developed and delivered to farmers by IITA over the past four decades. These varieties have varying degrees of resistance to insect pest attacks. A field study was established in northern Nigeria to determine the response to insecticide spraying of old cowpea varieties developed in the late 1970s and new varieties developed in the 2000s in order to determine whether new varieties have lesser requirement for spraying with insecticides than the old ones. The result revealed that the new cowpea varieties developed in the 2000s require more spraying than the old varieties developed in the 1970s. Infestations by the insect pests, maruca (Maruca virata Fabricius) and flower thrips (Megalurothrips sjostedti Trybom) were significantly less at zero and 1 spray for old varieties than for the new varieties. Old varieties also produced significant higher grain yield at zero and 1 spray compared with new varieties. Newer varieties require more spray to maximise yield gain.